PANCASILA – ROADBLOCK OR PATHWAY TO ECONOMIC DEVELOPMENT? - Marcus Marktanner; Maureen Wilson (MESP–FEB UNS, 2014)
While Pancasila was initially adopted as a normative value system to guide Indonesia’s political, social, and economic development after independence, the political implementation has always been subject to political dispute. Pancasila underwent three different stages: The Sukarno stage (1945-1967), the Suharto stage (1967-1998), and the post Suharto stage (1998-Present). During the Sukarno stage, Indonesia’s young democracy still proved to be too turbulent to guarantee national unity, leading Sukarno to centralize political power in the name of Pancasila. Suharto, inheriting a defunct economic system, on the other hand, also used Pancasila as a legitimization for centralizing his political power. By the end of the Suharto era, the value system of Pancasila had been largely associated with political abuse, leading to its stigmatization in postSuhartopolitics. At the same time, concerns for inequitable social development despite fast economic growth are on the rise. Indonesia is accordingly in danger of creating a void in its unifying normative value foundation that guides economic and public policy. This is especially true regarding the lack of safeguards against rising social injustice. This void may be filled by non-state actors like religious groups and radical movements and pose serious threats to Indonesia’s future political stability. A return to a national dialogue regarding how to translate Pancasila’s normative value system into political and economic reality is necessary to turn Pancasila from a roadblock to a pathway of sustainable development.Keywords: Pancasila, Pancasila Economics, Historical Analysis, Socioeconomic Development